GEOPOLITICAL ASPECTS OF ENERGY SECURITY AND ENVIRONMENTAL SECURITY IN THE REPUBLIC OF SERBIA - Stajić, Ljubomir; Radivojević, Nenad; Mirković, Vladan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Endangering of the environment today is largely due to the pursuit of energy security, respectively the need for a large amount of it. In this regard, the subject of our research is to determine the interdependence and impact of energy security on environmental security, and vice versa, as well as identifying the sources, forms and carriers of endangering energy security and environment security. In order to determine this, bearing in mind that "race for remaining resources" in the world in the last few decades has been particularly intensified; it is necessary to consider contemporary geopolitical trends and their impact on the security of small countries, including the Republic of Serbia. Namely, the key factors of energy security are the existence, production (exploitation), transit and use of fossil fuels (coal, oil and natural gas). The Republic of Serbia has significant quantities of coal reserves, while in the case of oil and natural gas, its energy needs are largely met by imports. The geographical and geo-strategic positions of the Republic of Serbia in the area of ​​Southeastern Europe (and the Western Balkans) indicate its extremely favorable position as a transit country. Achieving its energy security depends largely on viewing and understanding contemporary geopolitical trends. The geopolitical (and hegemonic) aspirations of large countries have often led (and still do) to provoking certain conflicts, crises, and even open armed conflicts that, among other things, have impact on endangering the environment.